Unleashing Nepal’s Demography as Soft Power - Shakya, Sujeev (Journal of Foreign Affairs, 2021)
For small powers like Nepal, enhancement of soft power to achieve national interests and economic aspirations is important. For this, however, the aspect of Nepal’s demography has not been considered as a source for advancing Nepal’s soft power. Owing to the same research gap, this study emphasises how Nepal’s demographics can be a significant facet to enhancing Nepal’s soft power. With the same objective, this paper has essentially explored the unexplored territories of demography, migration and also women’s contributions to Nepal’s economy to boost up Nepal’s soft power ambition. Stressing on the changed narrative away from the conventional notion of “yam between two boulders”, the study introduces the idea of “Global Nepali” as a component to enhance Nepal’s soft power, considering the changing demography of Nepal. Also, by shedding light on the contribution of Nepali women in Nepal’s economic growth and its potentiality to advance Nepal’s soft power, this study reiterates that the soft power of a country like Nepal lies in the hearts of its people and what they have to offer to the world.